2015
DOI: 10.4236/ijohns.2015.44054
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation Grafts in Septorhinoplasty: Our Experience

Abstract: Augmentation of nasal tip and/or dorsum forms the keystone of any Septorhinoplasty surgery. The grafts available for augmentation are numerous and varied. Choice of the graft depends upon the type of augmentation required, patient characteristics and, most importantly, the surgeon. In this article, we would like to present our experience with various augmentation grafts. In our experience, autografts are best grafts for augmentation. But in cases of revision surgeries or deficiency of autografts, allografts ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An external rhinoplasty approach destroys some of the minor nasal tip support mechanisms that subsequently needed to be repaired 9 . Strut said to be a versatile method to avoid collapse of the tip by preventing it from falling off the cartilaginous nasal pyramid, and that strut graft maintains nasal tip projection 10 . We found that nasal tip projection slightly decreased from 0.63 to 0.62 in strut group of patients by using Goode ratio.…”
Section: Discussionmentioning
confidence: 99%
“…An external rhinoplasty approach destroys some of the minor nasal tip support mechanisms that subsequently needed to be repaired 9 . Strut said to be a versatile method to avoid collapse of the tip by preventing it from falling off the cartilaginous nasal pyramid, and that strut graft maintains nasal tip projection 10 . We found that nasal tip projection slightly decreased from 0.63 to 0.62 in strut group of patients by using Goode ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous grafts are more available, ideal, more natural, and resulting in minimal immunological reactions. 7,8 Cartilage is the most commonly used graft because it could be used as a structural graft and fill the organ recipient's space, and it is easy to adjust to the recipient's shape and size. The graft could be harvested from the 5 th to 9 th costal ribs, but the 7 th rib is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…The donor site morbidity included pain and incision scar. 8 Fat grafts are known to be the right choice for soft tissue augmentation material in plastic surgery. In early 1893, free fat had been used by Neuber to fill soft tissue defects.…”
Section: Introductionmentioning
confidence: 99%